Development of Cefotaxime Impregnated Chitosan as Nano-antibiotics: De Novo Strategy to Combat Biofilm Forming Multi-drug Resistant Pathogens - Jamil, Bushra; Habib, Huma; Abbasi, Shahid A.; Ihsan, Ayesha; Nasir, Habib; Imran, Muhammad (Frontiers in Microbiology, 2016)
Frequent incidents of antibiotic-resistant biofilm forming pathogens in community-associated and hospital-acquired infections have become a global concern owing to failure of conventional therapies. Nano-antibiotics (NABs) are de novo tools to overcome the multi-drug resistant mechanisms employed by the superbugs. Inhibition of biofilm formation is one of those strategies to curb multi drug resistance phenomenon. In the current study, the anti-biofilm and antibacterial potential of newly synthesized cefotaxime loaded chitosan based Nano-antibiotics (NABs) have been investigated. Both bare and cefotaxime loaded NABs were prepared by ionotropic gelation method. They were found carrying positive zeta potential of more than +50 mV, indicating highly stable nano-dispersion. Moreover, microscopic studies revealed their size as less than 100nm. Nano-antibiotics (NABs) were tested against clinical isolates of multi drug resistant Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli and methicillin resistant Staphylococcus aureus (MRSA) and wherein they demonstrated broad-spectrum anti-biofilm and anti-pathogenic activity. Thus, in vitro synergistic action of cephalosporin drugs and chitosan polymer at nano-scale in contrast to free antibiotics can be an improved broad-spectrum strategy to thwart resistance mechanisms in both Gram positive and Gram negative resistant pathogens.